The complete chloroplast genome sequence of a rambler rose, Rosa wichuraiana (Rosaceae) - Wei-Hua Cui; Mi-Cai Zhong; Xin-Yu Du; Xiao-Jian Qu; Xiao-Dong Jiang; Yi-Bo Sun; Dan Wang; Sui-Yun Chen; Jin-Yong Hu (Mitochondrial DNA. Part B. Resources, 2020)
The rambler Rosa wichuraiana Crép. is an important founder species during modern rose domestication. However, the chloroplast genome (plastome) of this wild species remains unavailable. Here, we assembled the complete chloroplast genomes for two genotypes of R. wichuraiana. Both plastomes were typical quadripartite circular with 156,500/156,504 bp in length, comprising a large single-copy (LSC) region of 85,651/85,660 bp and a small single-copy (SSC) region of 18,751/18,744 bp, separated by two inverted repeat (IR) regions of 26,049/26,050 bp, respectively. Both plastomes encoded 113 unique genes, including 79 protein-coding genes, 30 tRNA genes, and 4 rRNA genes. Phylogenetic reconstruction with several rose plastomes revealed that both genotypes were sisters to a clade including Rosa luciae, Rosa multiflora, and Rosa maximowicziana.